PRODUKSI HANDSANG âHANDSANITIZER BERBAHAN UTAMA PELEPAH PISANGâ SEBAGAI PROGRAM PERCONTOHAN UMKM - Ariningsih, Umi; Abdul Aziz, Hamas Musyaddad (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Banana (Musa spp) is a very big agricultural commodity in Indonesia. Its easy grows up characteristic in Indonesia, making it cultivated a lot by community. One part of banana that still underutilized is banana frond. Banana frond has enough useful content in health sector. There are tannin and saponin which functioned as natural antiseptic substances. In addition, banana sap containing two substances that have a role in curing the wound, which are flavonoid and ascorbic acid. Rawasari village, Tembalang districts, Semarang city is marginal village that has great banana potency but human resources quality there still uneducated or unable to utilize natural resources in that village, based on per January 2014 data , there were 47% population are not entering elementary school, and most of them having professions as farm workers. Looking those background we make innovation that can utilize banana waste to be hand sanitizer with brand name is handsang. Its approaching method by PRA method (Participatory Rural Appraisal), which is understanding condition in the target area, so that community can participate actively. Implementation methods are socialization, three times meeting mentoring, and evaluation as partner introduction. The manufacturing process are taking banana frond , taking banana extract by using juicer, extract frond banana filtration, sterilization, appropriate dose measurement, materials mixing, and packaging. Until now, there is Women Business Group that has been established, that has been registered in UMKM Semarang, and still queue to get brand right to register in 2015 period.Keywords: Banana, banana sap, Rowosari, hand sanitizer, handsang